The Relationship Between Service Quality and Patient Satisfaction in RSGM-P UNSRAT Outpatient Unit - Jean Siska Roma Tairas; Greta Jane Pauline Wahongan; Erwin Gidion Kristanto (LPPM Universitas Harapan Bangsa, 2024)
High-quality healthcare services are crucial for ensuring safety, accessibility, and effectiveness, which ultimately enhance patient satisfaction and support hospital accreditation. This research sought to examine the connection between service quality and patient satisfaction in the Outpatient Unit of RSGM-P UNSRAT. A quantitative cross-sectional design was applied from January to September 2024. The population included patients receiving treatment at RSGM-P UNSRAT, with a sample of 200 patients selected through purposive sampling based on inclusion criteria such as being ≥18 years old and having received at least one treatment. Data were collected by using questionnaire and analysis through univariate, bivariate, and multivariate techniques. The univariate analysis indicated that over 50% of patients were satisfied with the service quality. Bivariate analysis showed significant associations between patient satisfaction and all five service quality dimensions—reliability, Tangibles, assurance, responsiveness, and empathy (p<0.05). Multivariate analysis revealed that assurance was the most dominant factor influencing satisfaction, with an odds ratio of 5.334. The study concludes that service quality is significantly related to patient satisfaction, with assurance being the most influential factor. It recommends regular patient satisfaction surveys to identify improvement areas and suggests further research into other factors affecting service quality.